Views of advance care planning in caregivers of older hospitalised patients following an emergency admission: A qualitative study. (February 2022) - Bielinska, Anna-Maria; Archer, Stephanie; Soosaipillai, Gehan; Riley, Julia; Darzi, Lord Ara; Urch, Catherine
This study explores the views of advance care planning in caregivers of older hospitalised patients following an emergency admission. Semi-structured interviews were conducted with eight carers, mostly with a personal relationship to the older patient. Thematic analysis generated three themes: (1) working with uncertainty – it all sounds very fine. . . what is the reality?, (2) supporting the older person – you have to look at it on an individual basis and (3) enabling the process – when you do it properly . The belief that advance care planning can support older individuals and scepticism whether advance care planning can be enabled among social and healthcare challenges are discussed.